The global economy as you've never seen it - Ramge, Thomas 1971-; Garcia-Landa, Adrian; Schwochow, Jan; Buchverlage, Ullstein (The Experiment, LLC, 2018)
"The goal of this book is to inspire you to explore the complex world of the economy. We want to provide understandable and entertaining access to it through the medium of the infographic. The Global Economy as You've Never Seen It is for everyone who finds it impossible to work their way through the business section of The New York Times each morning and who missed--or slept through--their Business and Econ 101 classes. Our expedition through the economic world begins with the smallest economic unit: the individual. Then, the perspective becomes progressively broader with each chapter. We'll take a look at companies, the national economy, and the world economy. We'll seek insights from the greatest minds of economic theory, and then think about how--if we avoid the dangers of greed--profits can be made without throwing the planet off balance and destroying the environment. Finally, we'll look into the future and speculate about new ways of thinking and new technologies that might make possible a new economy focused on the human being. This is no easy undertaking. The economic world is not only complex, but also enormous. At each way station of our journey, we have tried to translate into graphic form a broad spectrum of terms, contexts, concepts, and facts that seem essential to us. At many points we had to make decisions and accept trade-offs. The Global Economy as You've Never Seen It cannot, therefore, claim to be comprehensive--like an atlas that fully maps out Earth. Instead, the aim of our book is to arouse curiosity about intellectual terrain that is worth further exploration, not only because this territory is home to so many fascinating stories that have excited us--a journalist and a graphic designer--for two decades; but because, above all, economics connects everyone around the world. And that's precisely why it's so important to understand the global economy, and to see it as you've never seen it before."--Introduction